2016
DOI: 10.1176/appi.neuropsych.15070168
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Delusional Parasitosis and Complex Visual Hallucinations With Micropsia

Abstract: To the Editor: Complex visual hallucinations consist of people, deformed faces, animals, and complex scenes, which are often associated with various clinical diseases such as delirium tremens, Parkinson's disease, dementia with Lewy bodies, Charles Bonnet syndrome, and schizophrenia. 1,2 Delusional parasitosis can be defined as a delusional syndrome that primarily affects middle-aged and elderly individuals (mainly women) and consists of the belief that parasites plague the skin. 3 Of historical note, Berrios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Among four prior cases of delusional infestation diagnosed with DLB, two patients had visual hallucinations ( 7 9 ). Even in cases of suspected dementia in which a diagnosis of DLB had not been made, the coexistence of complex visual hallucinations and delusional infestation have been reported ( 15 17 ). The patient reported by Kanazawa and Hata was suspected of having Alzheimer’s dementia ( 15 ), and the case was reported before the publication of the first criteria for DLB ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among four prior cases of delusional infestation diagnosed with DLB, two patients had visual hallucinations ( 7 9 ). Even in cases of suspected dementia in which a diagnosis of DLB had not been made, the coexistence of complex visual hallucinations and delusional infestation have been reported ( 15 17 ). The patient reported by Kanazawa and Hata was suspected of having Alzheimer’s dementia ( 15 ), and the case was reported before the publication of the first criteria for DLB ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the patient reported by Rocha et al showed cognitive impairment, the diagnosis was unclear because the patient refused detailed examinations and evaluation and was also limited by visual deficits and hypoacusis ( 16 ). Another case reported by Hirakawa et al was suspected of having DLB, and donepezil hydrochloride was prescribed ( 17 ). Delusional infestation occasionally accompanies visual hallucinations ( 13 ), possibly suggesting the presence of a certain number of cases of undiagnosed DLB among patients with dementia and delusional infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of post-stroke delusion parasitosis were reported, especially for situations of right-side lesions (right temporoparietal cortex), the thalamus, and the putamen (the putamen influences visuotactile perception; through receptive cells, it projects to the parietal cortex, primary somatosensory cortex, and premotor cortex) [127,128].…”
Section: Dp and Strokementioning
confidence: 99%